The role of media linguistics in the media (Eurasian Journal of Philology Science and Education, 2019)
The modern world receives information easily. The main activity of the media is to provide real factsabout events taking place in society. Pragmatics of the media in the context of effective and contentdelivery of information to the addressee is accompanied by the use of different language units (phrases,phraseology, etc.) and with externally impressive codes (picture, music, etc.). Media linguistics has beenstudying the language of the media. Media linguistics focuses not only on the language of the media, butalso on the world of information, education, pragmatics, linguistic, speech culture and communicationethics.